RADT-22. RISING UTILIZATION AND REDUCED MEDICARE SPENDING OF SHORT-COURSE RADIATION THERAPY FOR PRIMARY CNS TUMORS IN ELDERLY ADULTS. (14th November 2022) - Tringale, Kathryn; Miller, Alexandra; Beal, Kathryn; Yang, Jonathan; Pike, Luke; Imber, Brandon
Abstract: INTRODUCTION: For elderly/frail glioma patients, shortening radiotherapy from 6 to 3 weeks (short-course RT [SC-RT]) is non-inferior to standard long course (LC-RT) though usage is estimated to be < 20%. We analyzed real-world utilization of SC-RT with/without systemic therapy in Medicare beneficiaries treated with RT for primary CNS tumors using CMS data on radiation episodes. METHODS: Radiation modality, year, age (65-74, 75-84, ≥ 85), and site-of-care (freestanding vs hospital-affiliated) were evaluated. Utilization of SC-RT (11-20 fractions) vs LC-RT (21-30 fractions) and systemic therapy was evaluated by multivariable logistic regression. Medicare spending over the 90-day episode was analyzed using multivariable linear regression (adjusted β coefficients reported). RESULTS: From 2015-2019, 9, 572 episodes were included (2, 966 [31%] SC-RT). SC-RT utilization increased (27% in 2015, 34% in 2019; OR 1.2 per year [95%CI:1.1-1.2]) and was associated with older age (age ≥ 85 vs 65-74, OR 7.0 [95%CI:5.7-8.7], hospital-affiliated sites (OR 1.2 [95%CI:1.1-1.4]), conventional RT (vs IMRT OR 2.8 [95%CI 2.4-3.3]), and lack of systemic therapy (OR 1.2 [95%CI:1.1-1.3]; p < 0.001 for all). Rise in SC-RT was concentrated in hospital-affiliated sites (interaction p = 0.005). Most (6, 629, 69%) received systemic therapy with no differences by site-of-care (p = 0.34). Systemic therapy utilization increased over time (67% in 2015, 71% in 2019; OR 1.1 per year [95%CI:1.1-1.1]) and was less likely for older patients, conventional RT, and SC-RT (p-value < 0.001 for all). SC-RT significantly reduced spending vs LC-RT (β=$8, 416, 95%CI:8, 317-8, 515), while spending modestly increased with systemic therapy usage (β=$316, 95%CI:220-409). CONCLUSIONS: While most Medicare beneficiaries received LC-RT for primary brain tumors, SC-RT utilization increased in hospital-affiliated centers; despite high-level evidence, discrepancy in SC-RT implementation by site-of-care persists and necessitates further investigation. Given RT course length had a greater impact on Medicare spending than systemic therapy, increased use of SC-RT in appropriate populations reflects an opportunity to increase high value care.